Atmavibyakti ra Kabita - Gautam, Krishna (Tribhuvan University Journal, 2010)
Not available. Key words: Kabita; Atma Tribhuvan University Journal Volume XVI, 1993 Page: 114-119 Uploaded date: 4 October, 2010